Planear a Cidade-Região do Futuro - Almeida Gonçalves, Carlos; Lourenço Marques, João (Coimbra University Press, 2025)
The permanence and recurrence of crisis contexts accelerates the need to rethink the theoretical and conceptual frameworks assigned to the mission of regional and urban planning. There is an urgent need to respond to the never foreseen and still unpredictable effects of the synchronisation of crises, gradually strengthening the resilience of urban systems. It is from this ambition that the future of societies will germinate. Building a polyhedral reflection on how to Plan the city-region of the future was taken on as an ambitious challenge for which we brought together knowledge from many disciplines mobilised by various institutions. The 13 chapters in this volume offer different and complementary approaches to planning the city-region of the future, seeing this as a model on which proposals for thinking, explaining and transforming are based. The publication is organised into 4 parts: I. Benchmarks; II. Benchmarks; II. Governance; III. Data Science; IV. Application to subsystems. The aim of this book is to serve as a reference for technicians, decision-makers, researchers, students and anyone interested in understanding and planning the city-region of the future. It is on this model of extended polycentric urbanisation that the reflections and proposals formulated here are based.